A new approach to supervisor design with sequential control Petri-net using minimization technique for discrete event system - Cansever, G.; Kucukdemiral, I. B. (SPRINGER LONDON LTD, 2006)
This paper proposes a systematic approach for the design of a supervisory controller for discrete event systems (DES) and their ladder logic diagrams (LLD). The method is based on Petri nets, which is used for modeling the systems. It involves, defining the control policy and simplifying it by using Espresso software to form the compiled controller by adding inhibiting and enabling arcs to the original model and then the method is used to drive structured ladder logic code. A design example is presented to clarify the full procedure.
Keywords: discrete event system; minimization technique; multi level logic conversion; programmable logic controller; sequential control Petri-net; supervisor design; Automation & Control Systems; Engineering